Neurodevelopmental disorders across the lifespan a neuroconstructivist approach - Farran, Emily K.; Karmiloff-Smith, Annette (Oxford : Oxford University Press, 2012)
This text presents evidence on development across the lifespan across multiple levels of description (genetic, brain cognitive, environmental). The authors use a well-defined disorder - Williams syndrome - to explore the impact of genes brain development, and behaviour as well as the individual's environment on development.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Developmental psychology; Cognition; Williams syndrome